Penerapan Full Day School Dalam Mengembangkan Budaya Religius di Sekolah Dasar Muhammadiyah 1 Menganti Gresik - Jesica Dwi Rahmayanti; Muhamad Arif (Institut Agama Islam Tribakti Kediri, 2021)
In general, elementary school-age children will feel bored when they are in school for longer, in contrast to the phenomenon that occurred at SD Muhammadiyah 1 Menganti. Students in this school actually look comfortable and very disciplined when they are at school, especially in terms of worship. Starting from this phenomenon, researchers want to know in depth about the application of full day schools in developing religious culture at SD Muhammadiyah 1 Menganti, with a focus on the problem of how to implement full day schools in developing religious culture at SD Muhammadiyah 1 Menganti ?. This study uses a qualitative method with a case study approach. Data collection techniques with observation, interviews, and documentation. The data analysis technique used the analysis of Miles and Huberman. Test the validity of the data by triangulation and reference adequacy. The results showed that full day school learning at SD Muhammadiyah 1 Menganti starts at 07.00 until 16.00. The learning is combined with Islamic habituation which becomes an effort in developing religious culture in schools, and is formed in several activities, namely: shaking hands and saying greetings to teachers, congregational prayers (dhuha prayer, midday prayer, Asr prayer, Friday prayer) , Koran morning, mutual respect and tolerance, tahfiz juz 30, Thursday morning study, study of women, Darul Arqom, MABIT, habituation of daily prayer, PHBI, social service, and habituation of giving. [Penelitian ini bertujuan untuk mendeskripsikan penerapan full day school dalam mengembangkan budaya religious di SD Muhammadiyah 1 Menganti Gresik. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dengan observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan analisis dari Miles dan Huberman. Uji keabsahan data dengan triangulasi dan kecukupan referensi. Hasil penelitian menunjukkan bahwa pembelajaran full day school di SD Muhammadiyah 1 Menganti Gresik dimulai pukul 07.00 sampai pukul 16.00. Pembelajarannya dipadukan dengan pembiasaan Islami yang menjadi suatu upaya dalam mengembangkan budaya religius di sekolah, dan terbentuk dalam beberapa kegiatan yaitu: berjabat tangan dan mengucapkan salam kepada guru, sholat berjama’ah (sholat dhuha, sholat dhuhur, sholat ashar, sholat jum’at), ngaji morning, saling hormat dan toleran, tahfiz juz 30, kajian kamis pagi, kajian keputrian, darul arqom, MABIT, pembiasaan doa sehari-hari, PHBI, bakti sosial, dan pembiasaan berinfaq]